Impact of Enhanced Recovery After Surgery Protocol Compliance on Outcome After Pancreatic Surgery: Results From a Certified ERAS Center - Alina S. Ritter, MD; Thilo Welsch, MD, FACS, MBA; Freya Brodersen, MSc; Julia Auinger, MD; Parisa Moll-Khosrawi, MD; Mara R. Goetz, MD; Jan Bardenhagen, MD; Christine Nitschke, MD; Tobias Schneider, BSc; Björn Wellge, MD; Anna Suling, PhD; Faik G. Uzunoglu, MD; et al. (Annals of Surgery Open)
Objective:. The aim was to evaluate the sustainability of the pancreatic Enhanced Recovery After Surgery (ERAS) program and the effect of ERAS items on patient morbidity and hospital stay. Background:. The current ERAS guideline recommendations encompass 27 items to improve recovery after pancreatoduodenectomy (PD). Methods:. Patients who underwent pancreatic resection at the University Hospital Hamburg-Eppendorf between February 2016 and June 2023 were included. The datasets were retrospectively collected from a central database. The effects of individual ERAS items and compliance on morbidity and hospital stay were assessed by uni- and multivariable analyses. Results:. In total, 594 patients who underwent PD (44.8%), distal pancreatectomy (14.6%), total pancreatectomy (17.8%), or other pancreatic resections (22.7%) were included. Of these, 90 patients (15.2%) achieved a high overall ERAS compliance of ≥70%. High compliance was associated with significantly less complications (Clavien–Dindo ≥ 3a), reduced 30-day mortality, and a shorter hospital stay. Early mobilization on the first postoperative day (POD1), restrictive intravenous fluid administration, and timely removal of urinary catheters were significant multivariable predictors for lower morbidity. Early mobilization on POD1 also correlated with reduced morbidity in the subcohort of PD cases. Conclusions:. The pancreatic ERAS protocol can be sustainably implemented and applied to both, PD and non-PD cases. A high level of compliance with the ERAS protocol after pancreatic resections correlated with improved outcomes but was achieved by less than one-fifth of patients. Early mobilization on POD1 and restrictive fluid management were key indicators for optimized short-term outcomes.